Appraisal-and-commendation policy and carbon emissions: Evidence from the national civilised city program in China - Huang, Guobin; Zhao, Guoqin; Huang, Nan (Frontiers in Energy Research, 2022)
Based on the theory of “Non-Economic Promotion Championship,” this paper takes Appraisal-And-Commendation (AAC) policy of National Civilised City (NCC) program in China as the research object, and analyses the influence and mechanism of the NCC on carbon emissions from the perspective of energy demand. We find that NCC reduces carbon emissions significantly, and this reduction effect continues to expand over time. Furthermore, the NCC reduces carbon emissions through two mechanisms: First, the NCC reduces carbon emissions by slowing urbanisation. This mechanism mainly functions in big cities, megacities, and super cities, and does not function in small and medium cities. Second, the NCC reduces carbon emissions by promoting industrial restructuring from secondary industry to tertiary industry. This carbon reduction effect is a pure structural adjustment effect, regardless of any effects on technological level and productivity. Moreover, there are regional differences in the reduction of carbon emissions by NCC through industrial restructuring in two dimensions: In the first dimension, compared with the western region and the northeast region, the eastern and central regions are more able and willing to reduce carbon emissions through industrial restructuring. In the second dimension, compared with the northern region, the southern region is more likely to reduce carbon emissions through industrial restructuring.